Are wildfires an adapted ecological cue breaking physical dormancy in the Mediterranean basin?. Issue 2 (June 2015) - Jaganathan, Ganesh K.
Abstract Many studies have claimed that fire acts as the chief ecological factor cueing dormancy break in seeds with a water-impermeable seed coat, i.e. physical dormancy (PY), in Mediterranean ecosystems. However, a proposal is made that seasonal temperature changes must be viewed as more meaningful dormancy-breaking cues because: (1) fire is erratic and may break PY in seasons during which seedlings cannot complete their life cycle; (2) fire may not occur for long periods, thereby only providing an opportunity for dormancy break and germination once in every several years; and (3) if fire opens the specialized anatomical structures called 'water gaps', in seconds, their evolutionary role of detecting environmental conditions becomes irrational. Although fire breaks dormancy in a proportion of seeds, given the risk of seed mortality and the post-fire environment providing cues for dormancy break, it is suggested that fire might possibly be an exaptation.